Flavor Profile in Fresh-squeezed Juice of Four Thai Lime Cultivars: Identification of Compounds that Influence Fruit Selection by Master Chefs - Korkitpoonpol, Jutamas; Suwannaprom, Nattamon; Keeratipibul, Suwimon; Wongravee, Kanet; Phuwapraisirisan, Preecha; Xiao, Li; Boonbumrung, Sumitra; Ngamchuachit, Panita (Applied Science and Engineering Progress, 2020)
The flavor and sensory profiles that influenced the selection of 4 commercial Thai lime cultivars (Citrus aurantifolia Swingle cv. ‘Pan Rumpai’, ‘Pan Puang’, and ‘Pan Pijit’ and Citrus latifolia Tanaka cv. ‘Tahiti’) by Thai chefs were examined. Twenty-eight volatiles (7 monoterpenes, 13 sesquiterpenes, 4 monoterpene alcohols, 1 aldehyde, 2 monoterpene aldehydes, and 1 monoterpene ester) and 9 non-volatiles (citric acid, malic acid, succinic acid, ascorbic acid, sucrose, fructose, glucose, limonin, and naringin) contributing to the flavor of Thai lime juice were identified using dynamic headspace-gas chromatography-olfactometry-mass spectrometry and high-performance liquid chromatography, respectively. An interview of master chefs and an acceptance test of culinary students revealed that Pan Puang was the most preferred lime cultivar owing to its moderate sour taste and its unique floral aroma contributed by terpinolene and linalool, along with its low content of β-myrcene, which contributes to balsamic and pungent aroma notes.